2014
DOI: 10.1016/j.ydbio.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Rab23 regulates Nodal signaling in vertebrate left–right patterning independently of the Hedgehog pathway

Abstract: Asymmetric fluid flow in the node and Nodal signaling in the left lateral plate mesoderm (LPM) drive left-right patterning of the mammalian body plan. However, the mechanisms linking fluid flow to asymmetric gene expression in the LPM remain unclear. Here we show that the small GTPase Rab23, known for its role in Hedgehog signaling, plays a separate role in Nodal signaling and left-right patterning in the mouse embryo. Rab23 is not required for initial symmetry breaking in the node, but it is required for expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 82 publications
(89 reference statements)
0
41
0
Order By: Relevance
“…However, an in vivo study has demonstrated that Rab8 is dispensable for ciliogenesis, as cilia are formed normally in Rab8a and Rab8b double mutant mice (Sato et al, 2014). Similarly, cell culture studies have suggested that Rab23 is involved in ciliogenesis (Lim and Tang, 2015;Yoshimura et al, 2007), but the in vivo evidence does not support that (Eggenschwiler et al, 2001;Fuller et al, 2014). Thus, to our knowledge, no Rab proteins have been so far linked to ciliogenesis in vivo and Rab34 is the first one shown to be required for ciliogenesis in vivo.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, an in vivo study has demonstrated that Rab8 is dispensable for ciliogenesis, as cilia are formed normally in Rab8a and Rab8b double mutant mice (Sato et al, 2014). Similarly, cell culture studies have suggested that Rab23 is involved in ciliogenesis (Lim and Tang, 2015;Yoshimura et al, 2007), but the in vivo evidence does not support that (Eggenschwiler et al, 2001;Fuller et al, 2014). Thus, to our knowledge, no Rab proteins have been so far linked to ciliogenesis in vivo and Rab34 is the first one shown to be required for ciliogenesis in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Rab23 also maintains ciliary steady state of Smo (Boehlke et al, 2010). Nevertheless, cilia form normally in Rab23 mutant mice (Fuller et al, 2014) and, so far, no Rab proteins have been linked to ciliogenesis in vivo. In addition, no Rab GTPases have been shown to regulate the fusion of preciliary vesicles to generate ciliary vesicleseven in cultured cells.…”
Section: Introductionmentioning
confidence: 99%
“…Chi et al (21) reported that Rab23 could negatively regulate Gli1 in a SUFU-dependent manner. However, Fuller et al (22) reported that Rab23 promotes nodal signaling in vertebrate left-right patterning independent of the Shh signaling pathway. In the present study, it was demonstrated that Rab23 upregulated ABCG2 expression via the Shh-Gli signal pathway in OC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present study posed and verified the hypothesis that the hedgehog signaling pathway activates the PI3K/AKT pathway, which subsequently upregulates the expression of MMP-2 and MMP-9 at the mRNA and protein level, thereby mediating GBM migration and invasion. The hedgehog signaling pathway has a vital role in the control of cell differentiation, cell proliferation and embryonic development (5,7,12). According to recent studies, aberrant activation of hedgehog signaling is linked to the aggressiveness of multiple tumor types, including GBM (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The hedgehog signaling pathway is essential for embryonic patterning and cancer development (5)(6)(7). The hedgehog protein family includes desert hedgehog, Indian hedgehog and sonic hedgehog (SHH).…”
Section: Introductionmentioning
confidence: 99%